Nutrition education strategies to promote vegetable consumption in preschool children - The Veggies4myHeart Project - Braga-Pontes, Cátia (2022)
Funding: We are very grateful to the principals, teachers, staff, and families of the preschools with which we partnered on this project. Financial support: This work was funded by ‘Challenges in Cardiology Accelerator Program 2018’and by Portuguese national funds provided by Fundação para a Ciência e Tecnologia (FCT) (UIDB/ 05704/2020 and UIDP/05704/2020).